Interactions of Isoquinoline Alkaloids with Transition Metals Iron and Copper - Mst Shamima Parvin; Jakub Chlebek; Anna Hošťálková; Maria Carmen Catapano; Zuzana Lomozová; Kateřina Macáková; Přemysl Mladěnka (Molecules, 2022)
Data on alkaloid interactions with the physiologically important transition metals, iron and copper, are mostly lacking in the literature. However, these interactions can have important consequences in the treatment of both Alzheimer’s disease and cancer. As isoquinoline alkaloids include galanthamine, an approved drug for Alzheimer’s disease, as well as some potentially useful compounds with cytostatic potential, 28 members from this category of alkaloids were selected for a complex screening of interactions with iron and copper at four pathophysiologically relevant pH and in non-buffered conditions (dimethyl sulfoxide) by spectrophotometric methods in vitro. With the exception of the salts, all the alkaloids were able to chelate ferrous and ferric ions in non-buffered conditions, but only five of them (galanthine, glaucine, corydine, corydaline and tetrahydropalmatine) evoked some significant chelation at pH 7.5 and only the first two were also active at pH 6.8. By contrast, none of the tested alkaloids chelated cuprous or cupric ions. All the alkaloids, with the exception of the protopines, significantly reduced the ferric and cupric ions, with stronger effects on the latter. These effects were mostly dependent on the number of free aromatic hydroxyls, but not other hydroxyl groups. The most potent reductant was boldine. As most of the alkaloids chelated and reduced the ferric ions, additional experimental studies are needed to elucidate the biological relevance of these results, as chelation is expected to block reactive oxygen species formation, while reduction could have the opposite effect.